Pengaruh Intervensi Psikoedukasi Terhadap Tingkat Depresi Pada Pasien Kanker Serviks Yang Menjalani Kemoterapi Di RSUD Dr. Moewardi Surakarta - Ratna Purwaningsih, Fatimah; , Okti Sri Purwanti, S.Kep.,M.Kep.,Ns.,Sp.Kep.,MB (2017)
Cervical cancer is the second largest cancer after breast cancer suffered by many women. Various kinds of cancer treatment one of them is chemotherapy that cause many side effects for the patient, side effects can cause the patient experiencing psychic disorder that is depresi. The impact can be reduced by providing psycho-education. The purpose of this study was to determine the difference of depression level in cervical cancer patients who undergoing chemotherapy at RSUD Dr. Moewardi Surakarta with psychoeducation intervention. This type of research is quantitative, preexperimental with one group pre-post test design technique,sampling is purposive sampling, with 20 respondent. The research instrument used BDI questioner and data analysis is Wilcoxon.. The result of the analysis of depression level depression was obtained ρ value 0.001 with α = 0,05 (ρ <α) it can be concluded that there is influence significantly before and after given psychoeducation intervention to depression level. Suggestions for health workers, especially inpatient nurses, to further increase their concern to overcome the psychological problems experienced by patients with psychoeducation interventions in the implementation of nursing. Keywords: Psychoeducation, Depression, Cervical Cancer